Toxic bachelors - Steel, Danielle (New York : Delacorte Press, 2005)
Three bachelors embark on a journey to the Mediterranean where they face women who challenge their deepest relationship phobias, sparking big changes in the once- carefree trio that just might put an end to their carousing.
Keywords: Bachelors -- Fiction; Man-woman relationships -- Fiction; Male friendship -- Fiction; New York (N.Y.) -- Fiction; Love stories